Mengintegrasikan Critical Thinking dalam Pembelajaran Kontekstual IPA di SMPN 2 Wirosari - Purwanti Purwanti; Endang Fauziati; Ahmad Fathoni (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Critical thinking is an important skill that must be possessed by students. Critical thinking needs to be integrated in contextual learning of Natural Sciences (IPA) at SMPN 2 Wirosari, Wirosari District, Grobogan Regency, Central Java Province. The purpose of this study is to describe the integration of critical thinking in planning, implementation, and evaluation of contextual science learning at SMPN 2 Wirosari. The type of research used is qualitative research with a case study design. The research data were collected using interview, observation, and documentation techniques. The results of this study are as follows: 1) In planning: critical thinking is integrated in the preparation of annual programs, semester programs, syllabus, lesson plans, KKM, materials, teaching materials, classroom/laboratory layouts, and learning media in accordance with the principles of contextual learning; 2) In the implementation: critical thinking integration is carried out using a scientific approach by applying the stages, namely: students observing, motivating students to ask questions, collecting information, analyzing data, discussing and explaining it in front of a presentation; and 3) Evaluation: the integration of critical thinking is carried out by evaluating the curriculum, learning activities that include preparation, implementation of learning, and assessment using academic supervision instruments. Competencies evaluated include competencies: pedagogic, professional, personality, and social. The integration of critical thinking in contextual science learning at SMPN 2 Wirosari went well.